Позиціонування контролінгу маркетингу та збуту в системі менеджменту підприємства - Долінська, Раїса Григорівна; Бурма, А. В. (НТУ "ХПІ", 2015)
Узагальнені наукові підходи щодо визначення змістовного наповнення поняття «маркетинг-контролінг». Запропоновано варіант позиціонування служби контролінгу в системі управління групою інтегрованих підприємств. Сформульовані основні вимоги і запропоновані ознаки класифікації ключових показників маркетинг-контролінгу. Уточнена класифікація ключових показників контролінгу маркетингової діяльності через розширення класифікаційних ознак забезпечує збалансоване управління маркетингом, визначає конкретні шляхи розвитку і підвищення його ефективності, зокрема, дає змогу підпорядкувати цілі управління процесами маркетингу і збуту загальній меті корпоративного управління підприємствами.

Generalized scientific approaches to determine the content of the concept of "marketing controlling". The variant of controlling positioning service in the management group of integrated companies. The basic requirements and features of the classification proposed key indicators marketing controlling. Based on the analysis of the scientific literature on the content of the basic concepts of controlling marketing activities, it should be noted that in some cases the authors interpret them ambiguously, a large array of evolving concepts and generalized, very flexible transformation goes contents of many terms used by researchers. Organic combination of administrative processes in the system controlling marketing and marketing management, manifested in the fact that the marketing departments, each employee was acting within his specialization and competence of its tasks. This function organization, coordination and methodological provision of such service are controlling.
Positioning controlling marketing and sales management system enterprise
Keywords: системи управління підприємствами; позиціонування служби контролінгу; показники маркетинг-контролінгу; корпоративне управління підприємствами; marketing; controlling; positioning service controlling; key performance indicators Marketing Controlling